Survey Of Relationship Between Serum Procalcitonin And Infectious Diseases - M Rahimkhani; N Einollani; R Sharifian (Tehran University of Medical Sciences, 2011)
Background and Aim: Procalcitonin is prohormone of calcitonin and is made 116 amino acids. The normal value of procalcitonin is less than 0.5 ng/ml, that if this amount exceeds, infection is indicated. This poly-peptide is a marker for the diagnosis of primary infection. Increased amounts of procalcitonin is associated with infection; especially bacterial infections. Materials and Methods: 32 patients with liver cirrhosis and 16 healthy controls enrolled in this study were. Serum PCT levels in these subjects was measured. PCT level was measured by semi-quantitative method. Results: Patient group included 23 males and nine females with mean age of 45 years and SD= 17.44 years, the control group included 11 males and 5 females with mean age of 46 years and SD=15.5 years.The statistical analysis showed that there was significant difference between PCT levels in patients and controls (P<0.05).Furthermore PCT levels was significantly hgher in cirrhotic patients with hepatitisec background.Conclusion: Since these patients had no symptoms of infection and were hospitalized for endoscopy test and the PCT test was positive in 78.1% of cirrhotic patients ,whereas this ratio was 25% in the control group, the patients probably were infected and should be under proper treatment.